IRR AND XRF INVESTIGATIONS ON ANNUNCIATA BY ANTONELLO DA MESSINA TO TRACE THE ORIGINAL APPEARANCE OF THE BLU VEIL - Maria Francesca Alberghina (mediaGEO soc. coop., 2019)
A new diagnostic investigation on Annunciata painting by Antonello da Messina was carried out in situ, in the Sala di Antonello of the Galleria Regionale della Palazzo Abatellis in Palermo (Sicily). It was carried out by using INTRAVEDO scanner for IR Reflectography (InGaAs detector) and XRF mapping, in order to investigate, thanks to an innovative equipment, the blue painting area, and in particular, the area between the face of the Virgin and the blue veil (on her left side). This pictorial surface, probably altered in the past by a heavy cleaning (date back to the 19th century) that involved the face and hands, was not clearly understood during the previous scientific studies. The finding here has provided an important assumption for a correct historical - artistic reading of the original appearance of the subject and represent a scientific support to clarify the conservation history which leads the painting to its current state. The new studies provided a common understanding of the available archive information, previous restorations and diagnostic investigations carried out over time.